Cover Feature: In‐Cage Interactions in the Clathrate Superconductor Sr8Si46 (Chem. Eur. J. 4/2020). Issue 4 (11th December 2019) - Hübner, Julia‐Maria; Prots, Yurii; Schnelle, Walter; Bobnar, Matej; König, Markus; Baitinger, Michael; Simon, Paul; Carrillo‐Cabrera, Wilder; Ormeci, Alim; Svanidze, Eteri; Grin, Yuri; Schwarz, Ulrich
Abstract : Modern quantum chemistry has developed tools for bonding analysis in real space. The picture shows a crystal structure segment of the clathrate Sr8 Si46 combined with the distribution of pELI‐D, a function showing the orbital decomposition of the electron‐localizability indicator calculated within an energy window. The red isosurfaces visualize multi‐atomic covalent Sr−Si in‐cage bonding within large cavities of the framework. The computed values of the pELI‐D are shown for the (020) plane. More information can be found in the Full Paper by U. Schwarz et al. on page 830 .